Clearing the Pathway : Improving the Transition for Students Moving Between AQF Levels 5, 6 and 7 : Final Report. - McLaughlin, Patricia; Mills, Anthony; Davis, Peter; Saha, Swapan; Hardie, Mary (Office for Learning and Teaching, 2013)
Final report from a project that examines pathways between vocational education and higher education in the built environment. Less than 10% of the built environment workforce has higher education qualifications, compared with almost 50% with vocational education qualifications. In the built environment discipline, students are the least likely of all Australians to move between VET and HE or to continue their lifelong education. The barriers to AQF levels 5, 6, and 7 are precipitous for this discipline. As a key economic leader, the industry suffers critical skills gaps, with chronic shortages of professionally qualified graduates. This project examines tertiary pathways models in this discipline that account for successful high retention student transitions between these levels and using the DEMO evaluation matrix developed by NCSEHE, will isolate the critical success factors within these models. This evaluation and dissemination will allow outcomes to be adopted across other disciplines by all tertiary providers, thus enhancing opportunities for all students to participate in transitions that promote lifelong learning.